Bede Griffiths : a life in dialogue - Trapnell, Judson B., 1954- (SUNY series in religious studies., 2001)
"Bede Griffiths, O.S.B. Cam (1906-1993) was a pioneer in the meeting of faiths and of cultures in the second half of the twentieth century. This study of his pioneering work in intercultural and interreligious dialogue draws from meticulous research of Griffiths's writings and his sources, as well as numerous personal interviews with the man himself."--Jacket